Aplikasi Mobile Layanan Bantuan Pengadilan Negeri Tondano - Rina Mokodompit; Mohammad Mustain; Ferjenia Feybelia (JOINTER : Journal of Informatics Engineering, 2020)
Abstract— At present the use of mobile applications to help office work in various agencies, is a very important requirement. Like other district courts, the tondano district court still uses a manual system in terms of assistance services For example, visitors must wait for a long time to get information. The tondano district court assistance mobile application is very useful for employees, visitors, and developers of this application. This mobile application really help and easy used for tondano district court visitors to get information in the form of trial schedules, decision directories, ticket information, e-courts, and surveys conducted by tondano district courts. The research method used is the system development life cycle (SDLC). Testing this application uses black box testing which was tested by two people from the tondano district court with excellent testing results.